The Reintegration of Anomie Portrayed in Room by Emma Donoghue - Pamella Viviana Kusnadi; Karina Hanum Luthfia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study analyzes the social conditions that drove Ma, the mother in Emma Donoghue's novel Room (2010), to attempt suicide after escaping seven years of captivity. The novel is narrated from the perspective of Jack, Ma's five-year-old son, whose viewpoint frames every event, including his mother's psychological breakdown after their escape. While previous research has mostly interpreted Ma's crisis as a continuation of captivity trauma, this study argues that her breakdown is better understood through Émile Durkheim's (1897/1951) concept of anomie the collapse of normative coherence that leaves an individual without a stable social foundation. Using qualitative literary analysis, this study closely examines the post-escape sections of the novel, focusing on Ma's encounters with her family, a medical clinic, and the media. The findings suggest that the conflicting expectations imposed simultaneously by these institutions render Ma's reintegration structurally destructive rather than restorative. Her suicide attempt thus emerges not as a private act of despair but as a social fact produced by her position within a current that fails to accommodate her new identity. Her survival, however, is sustained not by institutional recovery but by the relational bond between Ma and Jack, which functions as the novel's balancing structure. This study contributes a Durkheimian sociological reading of Room, an approach not yet developed in existing literary scholarship on the novel.